RANCANG BANGUN APLIKASI LAYANAN PENGADUAN PADA DINAS PENDIDIKAN KABUPATEN OKU BERBASIS ANDROID MENGGUNAKAN ANDROID STUDIO - Lara Ditha, Ratrie; Faulina, Sri Tita; Wisnumurti, Wisnumurti (Universitas Mahakarya Asia, 2023)
The OKU Regency Education Office is one of the government agencies responsible for education in Ogan Komering Ulu Regency, which is on Jalan H. Moeh. Moeslimin No. 0085, Kemiling Tanjung Baru, East Baturaja District. From the results of the analysis carried out by the author at the OKU District Education Office, there is a problem, that is, people still make complaints manually, namely people come directly to the office, people make complaints through social media and people who have employee numbers send messages via WhatsApp. Data collection was carried out by visiting the place directly by means of interviews, observations and references. Supporting software in making this application is the Windows 10 operating system, Android Studio, Adobe XD, Android version 12. This research resulted in a Complaint Service Application at the OKU District Education Office containing history, vision and mission, organizational structure, field duties, public service standards, galleries, contacts and complaints.